2014
DOI: 10.1590/1981-8637201400030000071762
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of adenoid hypertrophy diagnosis by cephalometric radiography

Abstract: ObjectiveTo verify the reliability of adenoid hypertrophy diagnosis by cephalometric radiography. Method Results The correlation between the two examinations was considered moderately positive (0.5). Tests of validity and reliability reported a sensitivity of RESUMO ObjetivoVerificar a confiabilidade do diagnóstico da hipertrofia das adenóides por meio da cefalometria. MétodosTrinta indivíduos do gênero masculino, com idades entre 12 e 15 anos, respiradores bucais ou não, foram selecionados e neles realizado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since diagnostic records can be used before routine orthodontic treatment and thus avoid giving the patient an additional dose of radiation [19,20], lateral cephalometry radiography was used in this study. Studies have shown that the use of lateral cephalometry to measure the nasopharyngeal area is quite valid [21,22]. Also, Aboudara, et al [23] Compared the lateral cephalometry and CBCT radiographs in the airway assessment and found that the lateral cephalometry provided a good indicator of the openness of the nasopharyngeal airway.…”
Section: Discussionmentioning
confidence: 99%
“…Since diagnostic records can be used before routine orthodontic treatment and thus avoid giving the patient an additional dose of radiation [19,20], lateral cephalometry radiography was used in this study. Studies have shown that the use of lateral cephalometry to measure the nasopharyngeal area is quite valid [21,22]. Also, Aboudara, et al [23] Compared the lateral cephalometry and CBCT radiographs in the airway assessment and found that the lateral cephalometry provided a good indicator of the openness of the nasopharyngeal airway.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoidectomy is considered quite a familiar surgical procedure for management of the condition. [7][8][9] Monocytes and macrophages form the core of innate immunity and maintaining the homeostasis among these cells can protect us from self-and external antigens. These immune cells can engulf bacteria by phagocytosis via the secretion of mediator components responsible for pro-inflammatory and antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%